Earthen ruins reinforcing mortar material based on hydraulic lime and MICP technology and preparation method and application thereof
By combining hydraulic lime with MICP technology, a modified soil site reinforcement mortar material was prepared, which solved the problems of low strength and poor durability of existing soil site restoration materials in the early stage, and achieved effective reinforcement and restoration of soil sites, with good mechanical properties and compatibility.
Patent Information
- Application Number
- CN202411976143.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Existing soil site restoration materials such as lime-cement composites have problems in early use, such as low strength, poor durability, easy to collapse and volume shrinkage. Cement is not conducive to the toughness of the mortar, resulting in a decrease in flexural strength, and the expansion stress of salt crystallization aggravates the damage to the soil site.
The soil site reinforced mortar material is adopted based on hydraulic lime and microorganism-induced calcium carbonate precipitation technology (MICP). By combining the modified soil with activated urea urea bacterial fluid, the gelling properties of natural hydraulic lime and ripe lime are used, and the curing effect of microorganisms is combined to improve the mechanical properties and durability of the mortar.
The early strength improvement, durability enhancement, excellent anti-seepage and good expansion resistance of the soil site reinforced mortar material has been achieved, and the performance is similar to the original soil site mortar, and it has good compatibility to meet the needs of soil site restoration.
Smart Images

Figure BDA0005223282590000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of earthen site building material repair, and in particular to an earthen site reinforcement mortar material based on hydraulic lime and MICP technology, and a preparation method and application thereof. Background Art
[0002] There are many ancient earthen sites and cultural relics in my country, among which Pingyao Ancient City is the most famous representative. As time goes by, the erosion of the natural environment, such as weathering, destroys the original building structure, causing it to fall off and collapse. At the same time, frequent human damage makes the building structure urgently need to be reinforced and repaired. There are many kinds of materials for repairing earthen cultural relics. Due to factors such as economic cost and construction conditions, lime-cement composite materials are selected for repair in most cases. However, air-hardening lime has many problems such as low early strength, slow coagulation and hardening, and poor durability. It is easy to disintegrate after contacting water and has obvious volume shrinkage, which limits its use alone in repair projects; cement is not conducive to the toughness of mortar, resulting in a decrease in flexural strength. After the two are compounded, the damage to the original earthen site is aggravated due to the expansion stress generated by salt crystallization and the formation of calcium aluminate in the crystal layer and pores.
[0003] Natural hydraulic lime (NHL) as a hydraulic cementing material can be traced back to the masonry cultural relics of the Minoan civilization in 3100 BC. As a lime material, hydraulic lime has both air-hardening and water-hardening characteristics, which are characterized by rapid coagulation and hardening, good air permeability, low soluble salt content, and is not easy to cause damage to the original building. It is a cementing material that meets the needs of earthen site restoration. Microbial induced calcium carbonate precipitation technology (MICP) is environmentally friendly and sustainable, but its use alone may have certain limitations in terms of strength improvement. Natural hydraulic lime has good adhesion and durability, and its use alone is difficult to fully meet the needs of earthen site protection. Therefore, combining the two is expected to provide a more effective solution for the protection of earthen sites.
[0004] In recent years, more and more scholars at home and abroad have conducted research on the optimization of natural hydraulic lime performance and proposed feasible solutions. Qingwen Ma et al. replaced NHL with sodium methyl silicate. The results showed that 0.3% sodium methyl silicate can enhance the compressive strength of NHL, reduce water absorption, and improve its resistance to dry-wet cycles. Kotteeswaran Santhanam et al. added carboxymethyl cellulose and alfalfa to replace NHL, and found that the early compressive strength was improved and the freeze-thaw resistance was stronger. M.MarBarbero-Barrera et al. replaced NHL5 with polypropylene fiber, and found that 2% of the fiber can increase the toughness and ductility of the mortar. The above research results are mostly reflected in the optimization of the performance of hydraulic lime mortar or mortar, mainly focusing on improving early strength and durability. For the restoration of earthen sites, the materials should meet the physical and chemical properties of "repairing the old as the old", and compatibility is the most important goal of repairing earthen sites.
[0005] Similarly, the restoration design process of earthen sites is mostly based on cement design, with mechanical properties as the focus of improvement. In contrast to cement repair materials, earthen site repair materials should have good compatibility and durability with earthen sites as the primary goal. The specific selection of repair materials should be combined with the actual situation of the site buildings, and the materials used in the site and their properties should be fully understood. Targeted evaluation and design based on the site materials and their shortcomings is the prerequisite for obtaining a well-compatible hydraulic lime repair mortar. The performance of the repair mortar and its preparation must be similar to the performance of the site being repaired.
[0006] Based on the analysis of the soil used in earthen sites and the mortar used for external repair, the mortar materials used for the repair of earthen site buildings should have the following basic characteristics: moderate mechanical properties (slightly higher than plain soil); excellent impermeability; low shrinkage and reduced cracks after hardening; and no negative impact on the original soil in the later stage of the product. Therefore, it is of great significance to study a mortar material for earthen site reinforcement based on hydraulic lime and MICP technology and its preparation method. Summary of the invention
[0007] The purpose of the present invention is to provide a mortar material for reinforcing earthen sites based on hydraulic lime and MICP technology, and a preparation method and application thereof in view of the deficiencies in the prior art.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0009] The present invention provides a mortar material for reinforcing earthen ruins based on hydraulic lime and MICP technology. The raw materials of the mortar material for reinforcing earthen ruins include modified soil and activated urea micrococcus bacterial liquid.
[0010] The modified soil comprises a cementitious material, silt and water; the cementitious material comprises natural hydraulic lime and slaked lime, and the mass ratio of the natural hydraulic lime to the slaked lime is 2 to 4:2;
[0011] The mass ratio of the cementitious material to the silt is 23-27:100, and the mass ratio of the silt to water is 22-26:100;
[0012] The mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil is 5-25g:1L; in the activated urea micrococcus bacterial solution, the concentration of urea micrococcus is 17-23g / L.
[0013] Preferably, the 28d compressive strength of natural hydraulic lime is 2-7 MPa, and the apparent density is 0.82-0.9 g / cm 3 .
[0014] Preferably, the average particle size of slaked lime is 4-4.2 μm, and the density of silt is 1.6-1.8 g / cm 3 , the maximum dry density is 1.65~1.85g / cm 3 , the moisture content is 24~25.5%.
[0015] Preferably, the preparation method of the activated urea micrococcus bacterial liquid is: mixing urea micrococcus freeze-dried powder and bacterial culture solution and then curing to obtain the activated urea micrococcus bacterial liquid;
[0016] The curing is performed 2 to 3 times. After each curing, the supernatant is removed by centrifugation, and then the bacterial culture solution is added for curing again. In each curing, the volume ratio of the urea Micrococcus freeze-dried powder to the bacterial culture solution is 1:6 to 8.
[0017] Preferably, in each curing, the curing temperature is 27-33° C., the curing time is 45-52 h, and the curing is carried out at a rotation speed of 180-220 r / min.
[0018] Preferably, the culture solution comprises a buffered saline solution, yeast extract and ammonium sulfate, the mass volume ratio of yeast extract, ammonium sulfate and buffered saline solution is 18-22g:9-11g:1L; the pH value of the buffered saline solution is 9-9.5, and the concentration of the buffered saline solution is 0.1-0.15mol / L.
[0019] The present invention also provides a method for preparing the earthen ruins reinforcement mortar material based on hydraulic lime and MICP technology, comprising the following steps:
[0020] 1) performing a first mixing of silt, natural hydraulic lime and slaked lime, and performing a second mixing of the mixture and water to obtain modified soil;
[0021] 2) The activated urea micrococcus liquid is sprayed onto the modified soil and mixed, and the mixed material is rammed, compacted, scraped, and cured in sequence to obtain the earthen site reinforcement mortar material.
[0022] Preferably, the first mixing time is 3 to 5 minutes, and the second mixing time is 6 to 10 minutes.
[0023] Preferably, the number of tamping and compacting layers is 2 to 4, the curing temperature is 28 to 32° C., the curing relative humidity is 67 to 73%, the curing pH value is 8.8 to 9.2, and the curing time is 26 to 30 days.
[0024] The present invention also provides the application of the earthen site reinforcement mortar material based on hydraulic lime and MICP technology in the restoration of earthen sites.
[0025] The beneficial effects of the present invention include the following:
[0026] 1) The present invention conducts a scientific analysis on the original mortar used in the earthen ruins, and provides a mortar material for reinforcing the earthen ruins, which has a composition similar to the mortar used in history and has good compatibility with the earthen ruins. The mortar material for reinforcing the earthen ruins is based on hydraulic lime and can be used for repair projects after MICP treatment. The bacteria in the MICP technology are used to solidify calcium ions so that they produce better mechanical properties during the hardening process, thereby achieving a reinforcement effect. The mortar material has the characteristics of fast coagulation and hardening, moderate strength, high water resistance and excellent working performance.
[0027] 2) The mechanical strength of the earthen ruins reinforcement mortar material based on hydraulic lime and MICP technology of the present invention is significantly higher than the mechanical strength of the original earthen ruins soil block sample: the unconfined compressive strength of the original soil at 28 days is 0.7N / mm 2 The 28d flexural strength of the original soil is 0.2N / mm 2 The 28d unconfined compressive strength of the earthen ruins reinforcement mortar material of the present invention is higher than 2.7N / mm 2 , 28d flexural strength higher than 0.8N / mm 2 The earthen site reinforcement mortar material of the present invention has good workability and meets the normal construction requirements of earthen sites; it has good anti-seepage and anti-expansion properties, with an expansion rate of <0.1%; no cracks or falling off problems occur within a short period of time after reinforcement; it can solidify and harden to produce strength (12h) in both dry and humid environments, meeting the construction needs of different seasons.
[0028] 3) The present invention has the characteristics of simple preparation process, wide material sources, similar colors, moderate mechanical strength, excellent anti-seepage performance, and improved durability. Compared with cement materials, it does not cause damage to the original site structure, and meets the requirements of the dual carbon plan and the "sacrificial protection" principle required in site restoration projects. DETAILED DESCRIPTION
[0029] The present invention provides a mortar material for reinforcing earthen ruins based on hydraulic lime and MICP technology. The raw materials of the mortar material for reinforcing earthen ruins include modified soil and activated urea micrococcus bacterial liquid.
[0030] The modified soil comprises a cementitious material, silt and water; the cementitious material comprises natural hydraulic lime and slaked lime, and the mass ratio of the natural hydraulic lime to the slaked lime is 2 to 4:2;
[0031] The mass ratio of the cementitious material to the silt is 23-27:100, and the mass ratio of the silt to water is 22-26:100;
[0032] The mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil is 5-25g:1L; in the activated urea micrococcus bacterial solution, the concentration of urea micrococcus is 17-23g / L.
[0033] In the present invention, the mass ratio of natural hydraulic lime to slaked lime is preferably 2.5-3.5:2, more preferably 3:2; the mass ratio of cementitious material to silt is preferably 24-26:100, more preferably 25:100; the mass ratio of silt to water is preferably 23-25:100, more preferably 23.5-24:100.
[0034] In the present invention, the mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil is preferably 10-20 g:1L, more preferably 13-17 g:1L, and more preferably 15 g:1L; in the activated urea micrococcus bacterial solution, the concentration of urea micrococcus is preferably 19-21 g / L, and more preferably 20 g / L.
[0035] In the present invention, the 28d compressive strength of natural hydraulic lime is preferably 2 to 7 MPa, more preferably 3 to 6 MPa, and more preferably 4 to 5 MPa, and the apparent density is preferably 0.82 to 0.9 g / cm 3 , more preferably 0.84 to 0.88 g / cm 3 , more preferably 0.86 g / cm 3 .
[0036] In the present invention, the natural hydraulic lime is preferably natural hydraulic lime NHL2.
[0037] In the present invention, the average particle size of slaked lime is preferably 4 to 4.2 μm, more preferably 4.05 to 4.15 μm, and more preferably 4.096 to 4.12 μm; the density of silt is preferably 1.6 to 1.8 g / cm 3 , more preferably 1.63 to 1.76 g / cm 3The maximum dry density is preferably 1.65 to 1.85 g / cm 3 , more preferably 1.67 to 1.83 g / cm 3 The moisture content is preferably 24 to 25.5%, and more preferably 24.21 to 25.31%.
[0038] In the present invention, the cementitious material selects a high-doped natural hydraulic lime NHL2, which has the characteristics of air hardening and water hardening, so that the mortar can coagulate and harden in a dry or humid environment, thereby generating mechanical strength; in order to avoid the damage to the earthen site body caused by the rapid development of early strength during the repair process, slaked lime is used to partially replace the natural hydraulic lime NHL2, which avoids the problem of rapid development of early strength and allows the mortar to have a certain toughness. Slaked lime can also be used as a bacterial carbon source.
[0039] The urea micrococcus used in the present invention has the characteristics of strong decomposition ability and can quickly produce urease to catalyze the hydrolysis of urea. It combines with calcium ions and the like in the modified soil material to rapidly increase the mechanical properties in the early stage. The urea micrococcus can survive in a variety of environments and can still maintain a stable population size when the temperature, humidity and pH value fluctuate.
[0040] In the present invention, the method for preparing the activated urea micrococcus bacterial solution is preferably: mixing urea micrococcus freeze-dried powder and bacterial culture solution and then curing to obtain the activated urea micrococcus bacterial solution;
[0041] The curing is performed 2 to 3 times. After each curing, the supernatant is removed by centrifugation, and then the bacterial culture solution is added for curing again. In each curing, the volume ratio of the urea Micrococcus freeze-dried powder to the bacterial culture solution is 1:6 to 8.
[0042] In the present invention, the volume ratio of the urea Micrococcus freeze-dried powder to the bacterial culture solution is preferably 1:6.5-7.5, and more preferably 1:7.
[0043] In the present invention, it is preferred that the bacterial culture solution is placed on a sterile bench to cool after steam sterilization on the sterile bench. The temperature of the steam sterilization is preferably 120-130°C, more preferably 122-128°C, and more preferably 124-125°C. The time of steam sterilization is preferably 18-22 min, more preferably 19-21 min, and more preferably 20 min.
[0044] In the present invention, in each curing, the curing temperature is preferably 27-33°C, more preferably 28-32°C, more preferably 30°C, the curing time is preferably 45-52h, more preferably 46-50h, more preferably 48h, and the curing is preferably carried out at a rotation speed of 180-220r / min, more preferably 190-210r / min, more preferably 200r / min.
[0045] In the present invention, the urea micrococcus is maintained until white colonies appear, indicating that the strain is successfully activated.
[0046] In the present invention, the culture solution preferably comprises a buffered saline solution, a yeast extract and ammonium sulfate, and the mass volume ratio of the yeast extract, the ammonium sulfate and the buffered saline solution is preferably 18-22 g: 9-11 g: 1 L, more preferably 19-21 g: 9.5-10.5 g: 1 L, and more preferably 20 g: 10 g: 1 L; the pH value of the buffered saline solution is preferably 9-9.5, more preferably 9.2-9.3, and more preferably 9.25, and the concentration of the buffered saline solution is preferably 0.1-0.15 mol / L, more preferably 0.12-0.14 mol / L, and more preferably 0.13 mol / L.
[0047] The present invention also provides a method for preparing the earthen ruins reinforcement mortar material based on hydraulic lime and MICP technology, comprising the following steps:
[0048] 1) performing a first mixing of silt, natural hydraulic lime and slaked lime, and performing a second mixing of the mixture and water to obtain modified soil;
[0049] 2) The activated urea micrococcus liquid is sprayed onto the modified soil and mixed, and the mixed material is rammed, compacted, scraped, and cured in sequence to obtain the earthen site reinforcement mortar material.
[0050] In the present invention, the first mixing time is preferably 3 to 5 min, more preferably 3.5 to 4.5 min, more preferably 4 min, and the second mixing time is preferably 6 to 10 min, more preferably 7 to 9 min, more preferably 8 min.
[0051] In the present invention, the number of tamping and compacting layers is preferably 2 to 4 layers, more preferably 3 layers, the curing temperature is preferably 28 to 32°C, more preferably 29 to 31°C, more preferably 30°C, the curing relative humidity is preferably 67 to 73%, more preferably 68 to 72%, more preferably 70%, the curing pH is preferably 8.8 to 9.2, more preferably 8.9 to 9.1, more preferably 9.0, and the curing time is preferably 26 to 30 days, more preferably 27 to 29 days, more preferably 28 days.
[0052] The present invention also provides the application of the earthen site reinforcement mortar material based on hydraulic lime and MICP technology in the restoration of earthen sites.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] In the embodiment, the natural hydraulic lime is NHL2 produced by StAstier Company of France, and the apparent density of the natural hydraulic lime is 0.86 g / cm 3 , 28-day compressive strength is 5MPa, the chemical composition of natural hydraulic lime is: SiO 2 15.20%, CaO 74.39%, Fe 2 O 3 4.73%, SO 3 2.34%, K 2 O2.27%, Al 2 O 3 1.07%.
[0055] Slaked lime is industrial calcium hydroxide produced by Shanghai Jianghu Industrial Co., Ltd. It is a white powdery solid with an average particle size of 4.096 μm. The chemical composition of slaked lime is: Ca(OH) 2 93.61%, CaCO 3 4.39%, SiO 2 1.03%, MgO 0.62%, Na 2 O 0.35%.
[0056] The lyophilized powder of Micrococcus urea was purchased from the American Type Culture Collection (ATCC 700405) and stored in ampoules.
[0057] Bacterial culture medium was purchased from the American Type Culture Collection 4 -YE culture medium (deposit number ATCC 1376), 1L of bacterial culture medium consists of 1L of buffered saline solution (NH 4 Cl solution with a concentration of 0.13 mol / L), 10 g ammonium sulfate and 20 g yeast extract.
[0058] The silt was taken from the collapsed part of Pingyao Ancient City in Shanxi Province (original soil) and Pingyao soil field (new soil). The mass ratio of original soil to new soil was 1:1. The physical indicators of the silt are shown in Table 1.
[0059] Table 1 Physical indexes of silt
[0060]
[0061] Example 1
[0062] The preparation process of activated urea micrococcus bacterial solution is as follows: sterilize with high-temperature steam at 125°C for 20 minutes on a sterile bench, and then cool the bacterial culture solution on a sterile bench for use. Use a sterile pipette to draw 1.5mL of bacterial culture solution and inject it into an ampoule to dissolve 0.5g of urea micrococcus freeze-dried powder. Pour the dissolved urea micrococcus into a 9mL culture tube, mix evenly, draw a bevel, and inoculate it into a triangular flask containing new culture solution, and maintain it at 30°C and 200r / min for 48h. The activated bacterial solution is placed in a centrifuge (speed of 8000r / min) and centrifuged for 20min. After removing the supernatant, add new bacterial culture solution and shake well; maintain it again at 30°C and 200r / min for 48h (in each maintenance, the volume ratio of urea micrococcus freeze-dried powder to bacterial culture solution is 1:7). The activated urea micrococcus bacterial solution (concentration of 20 g / L) was placed in a 4°C refrigerator for later use.
[0063] Add silt, natural hydraulic lime NHL2 and slaked lime into a mortar mixer, continue stirring for 4 minutes until the color is uniform, then slowly add water and continue stirring for 8 minutes to obtain uniform modified soil; the mass ratio of natural hydraulic lime NHL2 and slaked lime is 3:2, the mass ratio of the total mass of natural hydraulic lime NHL2 and slaked lime to silt is 25:100, and the mass ratio of silt to water is 24.21:100;
[0064] The activated urea micrococcus bacterial solution was sprayed onto the surface of the modified soil (the mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil was 20g:1L), and the mixture was evenly mixed at the same time. The mixture was poured into a mold with an opening at the upper end for three layers of tamping and scraping. After that, it was cured for 28 days under the curing conditions of 30°C, 70% relative humidity and pH 9.0 to obtain the earthen site reinforcement mortar material.
[0065] The permeability coefficient of the earthen site reinforcement mortar material obtained in this example is 1.3×10 -5 cm·s -1 , showing good anti-seepage performance, 28d compressive strength is 3.6N / mm 2 , 28d flexural strength is 1.1N / mm 2 , expansion rate <0.1%. Similar to the mortar performance used in earthen ruins, it has good compatibility with the original earthen ruins and city walls. No cracks or falling off occurred within one year after reinforcement; it meets the requirements of composite mortar with hydraulic lime and MICP technology for the restoration of earthen ruins.
[0066] Example 2
[0067] The mass ratio of silt to water in Example 1 was changed to 23.38:100, the mass volume ratio of the activated urea micrococcus solution to the modified soil was changed to 15 g:1 L, and the other conditions were the same as in Example 1.
[0068] The permeability coefficient of the earthen site reinforcement mortar material obtained in this example is 1.8×10 -5 cm·s -1 , showing good anti-seepage performance, 28d compressive strength is 3.1N / mm 2 , 28d flexural strength is 1.0N / mm 2 , expansion rate <0.1%. Similar to the mortar performance used in earthen ruins, it has good compatibility with the original earthen ruins and city walls. No cracks or falling off occurred within one year after reinforcement; it meets the requirements of composite mortar with hydraulic lime and MICP technology for the restoration of earthen ruins.
[0069] Example 3
[0070] The mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil in Example 1 was changed to 10 g:1 L, and the other conditions were the same as in Example 1.
[0071] The permeability coefficient of the earthen site reinforcement mortar material obtained in this example is 2.7×10 -5 cm·s -1 , showing good anti-seepage performance, 28d compressive strength is 2.7N / mm 2 , 28d flexural strength is 0.8N / mm 2 , expansion rate <0.1%. Similar to the mortar performance used in earthen ruins, it has good compatibility with the original earthen ruins and city walls. No cracks or falling off occurred within one year after reinforcement; it meets the requirements of composite mortar with hydraulic lime and MICP technology for the restoration of earthen ruins.
[0072] Example 4
[0073] The preparation process of activated urea micrococcus bacterial solution is as follows: sterilize with high-temperature steam at 122°C for 22 minutes on a sterile bench, and then cool the bacterial culture solution on a sterile bench for use. Use a sterile pipette to draw 1.5mL of bacterial culture solution and inject it into an ampoule to dissolve 0.5g of urea micrococcus freeze-dried powder. Pour the dissolved urea micrococcus into a 9mL culture tube, mix evenly, draw a line on the bevel, and inoculate it into a triangular flask containing new culture solution, and maintain it at 28°C and 190r / min for 50h. The activated bacterial solution is placed in a centrifuge (speed of 8000r / min) and centrifuged for 20min. After removing the supernatant, add new bacterial culture solution and shake well; maintain it again at 28°C and 190r / min for 50h (in each maintenance, the volume ratio of urea micrococcus freeze-dried powder to bacterial culture solution is 1:6.5). The activated urea micrococcus bacterial solution (concentration of 19 g / L) was placed in a 4°C refrigerator for later use.
[0074] Add silt, natural hydraulic lime NHL2 and slaked lime into a mortar mixer, continue stirring for 3 minutes until the color is uniform, then slowly add water and continue stirring for 7 minutes to obtain uniform modified soil; the mass ratio of natural hydraulic lime NHL2 and slaked lime is 2.5:2, the mass ratio of the total mass of natural hydraulic lime NHL2 and slaked lime to silt is 24:100, and the mass ratio of silt to water is 23.5:100;
[0075] The activated urea micrococcus liquid was sprayed onto the surface of the modified soil (the mass volume ratio of the activated urea micrococcus liquid to the modified soil was 13g:1L), and the mixture was evenly mixed at the same time. The mixture was poured into a mold with an opening at the upper end for three layers of tamping and scraping. After that, it was cured for 28 days under the curing conditions of 28°C, 68% relative humidity and 9.1 pH value to obtain the earthen site reinforcement mortar material.
[0076] The permeability coefficient of the earthen site reinforcement mortar material obtained in this example is 1.5×10 -5 cm·s -1 , showing good anti-seepage performance, 28d compressive strength is 3.3N / mm 2 , 28d flexural strength is 1.05N / mm 2 , expansion rate <0.1%. Similar to the mortar performance used in earthen ruins, it has good compatibility with the original earthen ruins and city walls. No cracks or falling off occurred within one year after reinforcement; it meets the requirements of composite mortar with hydraulic lime and MICP technology for the restoration of earthen ruins.
[0077] Example 5
[0078] The preparation process of activated urea micrococcus bacterial solution is as follows: sterilize with high-temperature steam at 128°C for 18 minutes on a sterile bench, and then cool the bacterial culture solution on a sterile bench for standby use. Use a sterile pipette to draw 1.5mL of bacterial culture solution and inject it into an ampoule to dissolve 0.5g of urea micrococcus freeze-dried powder. Pour the dissolved urea micrococcus into a 9mL culture tube, mix evenly, draw a line on the bevel, and inoculate it into a triangular flask containing new culture solution, and maintain it at 32°C and 210r / min for 46h. The activated bacterial solution is placed in a centrifuge (speed of 8000r / min) for centrifugation for 20min, remove the supernatant and add new bacterial culture solution, shake well; maintain it again at 32°C and 210r / min for 46h (in each maintenance, the volume ratio of urea micrococcus freeze-dried powder to bacterial culture solution is 1:7.5). The activated urea micrococcus bacterial solution (concentration of 21 g / L) was placed in a 4°C refrigerator for later use.
[0079] Add silt, natural hydraulic lime NHL2 and slaked lime into a mortar mixer, continue stirring for 5 minutes until the color is uniform, then slowly add water, and continue stirring for 9 minutes to obtain uniform modified soil; the mass ratio of natural hydraulic lime NHL2 and slaked lime is 3.5:2, the mass ratio of the total mass of natural hydraulic lime NHL2 and slaked lime to silt is 26:100, and the mass ratio of silt to water is 25:100;
[0080] The activated urea micrococcus bacterial solution was sprayed onto the surface of the modified soil (the mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil was 17g:1L), and the mixture was evenly mixed at the same time. The mixture was poured into a mold with an opening at the upper end for three layers of tamping and scraping. After that, it was cured for 28 days under the curing conditions of 32°C, 72% relative humidity and 8.9 pH value to obtain the earthen site reinforcement mortar material.
[0081] The permeability coefficient of the earthen site reinforcement mortar material obtained in this example is 1.28×10 -5 cm·s -1 , showing good anti-seepage performance, 28d compressive strength is 3.7N / mm 2 , 28d flexural strength is 1.15N / mm 2 , expansion rate <0.1%. Similar to the mortar performance used in earthen ruins, it has good compatibility with the original earthen ruins and city walls. No cracks or falling off occurred within one year after reinforcement; it meets the requirements of composite mortar with hydraulic lime and MICP technology for the restoration of earthen ruins.
[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A mortar material for reinforcing earthen ruins based on hydraulic lime and MICP technology, characterized in that: The raw materials of the earthen ruins reinforcement mortar material include modified soil and activated urea micrococcus bacterial solution; The modified soil comprises a cementitious material, silt and water; the cementitious material comprises natural hydraulic lime and slaked lime, and the mass ratio of the natural hydraulic lime to the slaked lime is 2 to 4:2; The mass ratio of the cementitious material to the silt is 23-27:100, and the mass ratio of the silt to water is 22-26:100; The mass volume ratio of the activated urea micrococcus bacterial solution to the modified soil is 5-25g:1L; in the activated urea micrococcus bacterial solution, the concentration of urea micrococcus is 17-23g / L.
2. The earthen ruins reinforcement mortar material according to claim 1, characterized in that: The 28d compressive strength of natural hydraulic lime is 2-7 MPa, and the apparent density is 0.82-0.9 g / cm 3 .
3. The earthen ruins reinforcement mortar material according to claim 1 or 2, characterized in that: The average particle size of slaked lime is 4-4.2 μm, and the density of silt is 1.6-1.8 g / cm 3 , the maximum dry density is 1.65~1.85g / cm 3 , the moisture content is 24~25.5%.
4. The earthen ruins reinforcement mortar material according to claim 1, characterized in that: The preparation method of the activated urea micrococcus bacterial liquid is as follows: urea micrococcus freeze-dried powder and bacterial culture liquid are mixed and then maintained to obtain the activated urea micrococcus bacterial liquid; The curing is performed 2 to 3 times. After each curing, the supernatant is removed by centrifugation, and then the bacterial culture solution is added for curing again. In each curing, the volume ratio of the urea Micrococcus freeze-dried powder to the bacterial culture solution is 1:6 to 8.
5. The earthen ruins reinforcement mortar material according to claim 4, characterized in that: In each curing, the curing temperature is 27-33°C, the curing time is 45-52h, and the curing is carried out at a speed of 180-220r / min.
6. The earthen ruins reinforcement mortar material according to claim 4 or 5, characterized in that: The culture solution comprises a buffered salt solution, a yeast extract and ammonium sulfate, wherein the mass volume ratio of the yeast extract, the ammonium sulfate and the buffered salt solution is 18-22 g: 9-11 g: 1 L; the pH value of the buffered salt solution is 9-9.5, and the concentration of the buffered salt solution is 0.1-0.15 mol / L.
7. The method for preparing the earthen ruins reinforcement mortar material based on hydraulic lime and MICP technology according to any one of claims 1 to 6, characterized in that: The following steps are included: 1) performing a first mixing of silt, natural hydraulic lime and slaked lime, and performing a second mixing of the mixture and water to obtain modified soil; 2) The activated urea micrococcus bacterial liquid is sprayed onto the modified soil and mixed, and the mixed material is rammed, compacted, scraped, and cured in sequence to obtain the earthen site reinforcement mortar material.
8. The preparation method according to claim 7, characterized in that: The first mixing time is 3 to 5 minutes, and the second mixing time is 6 to 10 minutes.
9. The preparation method according to claim 7 or 8, characterized in that: The number of tamping and compacting layers is 2 to 4, the curing temperature is 28 to 32°C, the curing relative humidity is 67 to 73%, the curing pH value is 8.8 to 9.2, and the curing time is 26 to 30 days.
10. Use of the earthen site reinforcement mortar material based on hydraulic lime and MICP technology as described in any one of claims 1 to 6 in the restoration of earthen sites.
Citation Information
Patent Citations
High-performance durable natural hydraulic lime mortar for reinforcing and repairing rock and soil buildings and preparation method thereof
CN106927776A
Microbial curing-fiber reinforcement combined sandy soil modification method
CN109594552A
Slag adjusting hydraulic lime mortar for reinforcing and repairing earth construction, and preparation method thereof
CN110194638A
Method for improving microbial cemented sand
CN110965546A
Method for solidifying fractures of earthen ruins through microbial grouting
CN113235567A